Boosting Croatia’s Economic Resilience - World Bank (World Bank, Washington, DC, 2020)
It has taken Croatia over a decade to reach the level of output it enjoyed before the 2008 crisis, highlighting the economy’s weak resilience to shocks and the poor ability of its institutions and policies to ensure a faster recovery. The recovery started only in 2015 but in 2020 Croatia is again facing a deep downturn due to the COVID-19 (Coronavirus) pandemic that resulted in a global economic shock of unprecedented magnitude. Country’s economic resilience is under an influence of a range of institutional, economic, and social factors. Fiscal policy, as a demand management tool, and structural policies for increasing the flexibility of factor and product markets are at the core of Croatia’s resilience agenda. While certain features of the economy make Croatia particularly exposed to external shocks, fiscal position has been improved and labor and product market institutions have been made more flexible after the global financial crisis, so Croatia is now in a better position to recover from the crisis faster. First, once economic recovery gains momentum from the COVID -19 pandemic more ambitious fiscal targets and a fully binding national fiscal framework will help to rebuild the fiscal space needed for the countercyclical response in the next downturn. Second, streamlined regulation of permanent work contracts, coupled with active labor market policies and adequate social safety nets, will reduce labor market duality and facilitate adjustment to exogenous shocks. Third, speedy recovery from shocks will be facilitated by the improved functioning of product markets, with a reduced state footprint, less restrictive regulation of entry and conduct in service sectors, and improved bankruptcy practices to favor the seamless exit of market players. Reforms in these areas will help Croatia to recover more quickly from adverse shock and prepare the country for the next recession.